2009
DOI: 10.1007/s10551-010-0394-4
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility: One Size Does Not Fit All. Collecting Evidence from Europe

Abstract: ABSTRACT. This article serves as an introduction to the collection of papers in this monographic issue on ''What the European tradition can teach about Corporate Social Responsibility'' and presents the rationale and the main hypotheses of the project. We maintain that corporate social responsibility (CSR) is an ethical concept, that the demands for socially responsible actions have been around since before the Industrial Revolution and that companies have responded to them, especially in Europe, and that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 28 publications
3
87
0
4
Order By: Relevance
“…Whereas the government previously attempted to manage and control the business development through industrial policy, now, however, growth and profit have become prime motivators. The state has become weaker as an institution, but maintains a strong presence as a capitalist actor seeking a return on investments by holding many shares or even a majority in most large companies (Argandoña & Hoivik, 2009;Engelstad et al, 2003;Ihlen, 2011). It has been argued that even the large, publicly-owned, companies now operate with their own development and best interests at heart, rather than those of society Slagstad, 2001;K.…”
Section: The Globalized Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the government previously attempted to manage and control the business development through industrial policy, now, however, growth and profit have become prime motivators. The state has become weaker as an institution, but maintains a strong presence as a capitalist actor seeking a return on investments by holding many shares or even a majority in most large companies (Argandoña & Hoivik, 2009;Engelstad et al, 2003;Ihlen, 2011). It has been argued that even the large, publicly-owned, companies now operate with their own development and best interests at heart, rather than those of society Slagstad, 2001;K.…”
Section: The Globalized Responsibilitymentioning
confidence: 99%
“…Research has shown how the term corporate social responsibility (CSR) can be translated and interpreted in different ways in different countries according to their own historical context, where the size, age and the legitimacy of business in society all play a role (Argandoña & Hoivik, 2009). While the Scandinavian countries certainly share several traits and often are discussed as a whole (e.g., Gjølberg, 2009;McCallin & Webb, 2004;Morsing et al, 2007), it is also important to acknowledge the differences between these countries.…”
mentioning
confidence: 99%
“…On the other hand, SR practices are subject to an ongoing process of change, of institutional evolution. One of the most extended surveys of SR practices of companies in the area is that of Csá-for (2008) which deals with companies from the so-called Euro-Carpathian region 1 . Among the features of SR in the region the survey has found: the predominance of economic planning without regard for the community or the environment, and of improvised philanthropic activities as forms of SR, the disregard for unions and voluntary work, the use of SR mainly for marketing and public relations, rare publication of SR reports by companies and weak demand for SR practices on behalf of the public (Csáfor, 2008).…”
Section: International Variations Of Sr Practicesmentioning
confidence: 99%
“…In the international literature, the term "responsibility" generally has a moral connotation; it expresses the idea of "doing the right thing" in relation to people (stakeholders) who have expectations, who judge the company's work and towards whom the company also has a duty of accountability (Argandona & von Weltzien Hoivik, 2009). Acting responsibly should not be seen as the result of strategic consideration of both internal and external expectations in order to gain an advantage in terms of revenue and/or reputation; rather, any such advantages should be considered a natural consequence of behavior based on principles of a moral nature (Argandona & von Weltzien Hoivik, 2009).…”
Section: Review Of Literature On Csr and Social Communication Toolsmentioning
confidence: 99%